Happiness in the Covid-19 pandemic in Indonesia according to Nicomachean Ethics - Lodo, Alfredo S. (Technium Social Sciences Journal, 2021)
The Covid-19 pandemic, which has started to go global since 2020, has changed the order in almost all areas of life: socio-social, economic, political, religious, and so on. Difficult situations like this will certainly bring big changes, anxiety, worry, adversity, frustration, and so on. In a difficult situation like this, people will tend to start to lose direction and purpose in life. On the other hand, some parties still have optimism in the midst of the difficult situation of the Covid-19 pandemic. They have an expectation that this pandemic will end soon. Inevitably some of them still have happiness in the midst of this difficult situation. Given the pandemic situation that is still ongoing and still has an impact today as well as the various attitudes of the community in responding to it, the writer through this paper is interested in studying this phenomenon according to the Nikomachean Ethics. What is the happiness that is meant by the Nicomachean Ethics? What are the implications of this happiness during the Covid-19 pandemic in Indonesia?